2014
DOI: 10.1021/ja507295u
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Hydroamination of Unactivated Olefins Using a Co Catalyst for Complex Molecule Synthesis

Abstract: Functional group tolerance is one of the important requirements for chemical reactions, especially for the synthesis of complex molecules. Herein, we report a mild, general, and functional group tolerant intramolecular hydroamination of unactivated olefins using a Co(salen) complex, an N-fluoropyridinium salt, and a disiloxane reagent. This method, which was carried out at room temperature (or 0 °C), afforded three-, five-, six-, and seven-membered ring nitrogen-containing heterocyclic compounds and was compat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
78
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(86 citation statements)
references
References 60 publications
0
78
0
6
Order By: Relevance
“…Finally, the carbocation 70 would be trapped by the alcoholic solvent to form the hydroalkoxylated product 64 and HBF 4 , which could be then neutralized by the pyridine base. The same authors applied this co‐catalyzed formation of a carbocation to hydroamination, hydroarylation, and hydrooxycarbonylation reactions …”
Section: Planar Co(iii)‐hydride Complexesmentioning
confidence: 99%
“…Finally, the carbocation 70 would be trapped by the alcoholic solvent to form the hydroalkoxylated product 64 and HBF 4 , which could be then neutralized by the pyridine base. The same authors applied this co‐catalyzed formation of a carbocation to hydroamination, hydroarylation, and hydrooxycarbonylation reactions …”
Section: Planar Co(iii)‐hydride Complexesmentioning
confidence: 99%
“…[4e] Aconceptually different radical addition with nitroarenes was very recently added to the manifold of net hydroamination processes. [5] Baran et al reported the sequential combination of an Fe-catalyzed hydrogen atom transfer (HAT) [6] and an Fe-catalyzed reductive deoxygenation in ao ne-pot operation that allows the facile preparation of tert-a nd secalkyl aryl amines.B ased on some literature precedents, [7,8] ah ighly practical procedure was developed, which uses various alkenes,aromatic nitro compounds as Nelectrophiles, phenylsilane as the HATreagent, and iron(III) acetylacetonate as the pre-catalyst under thermal conditions (ethanol, 60 8 8C; Scheme 2). Isolated examples of Fe-catalyzed HATt o alkenes and subsequent reactions of the alkyl radicals with 1-butylnitrite to give nitrosoalkanes under similar conditions were reported by Mukaiyama and Kato in 1992.…”
mentioning
confidence: 99%
“…Building upon extensive recent reports in the area of metal-catalyzed hydrogen-atom transfer reactions to alkenes (MHAT), [10] we surmised that atertiary radical could be easily generated from the 1,1-disubstituted alkenes of type 3,a nd that under appropriate oxidative conditions,s uch as those from the group of Shigehisa, [11,12] cation generation could result by radical oxidation. Depending upon relative rates of oxidation and cyclization, either radical or cationic C À C bond-forming events would take place.Because we were most interested in developing cyclizations with C20 electron-withdrawing groups,w ei nitiated our studies with the diene 5a (Table 1), which was easily assembled by virtue of the oxygenation at C2.…”
Section: Resultsmentioning
confidence: 96%